Helminths associated with the threatened Alcatrazes snouted treefrog Ololygon alcatraz - Lisboa, Cybele Sabino; Brasileiro, Cinthia Aguirre; Dos Anjos, Luciano Alves [UNESP] (British Herpetological Society, 2023)
Ololygon alcatraz is a threatened treefrog endemic to a single small island in Brazil. Research on ecological interactions for this species is scarce, and nothing is known about parasitism. Thus, we investigated the presence of macroparasites of the gastrointestinal system of O. alcatraz. We found only two types of helminth, nematodes and acanthocephalans, both in the larval stages. Our results suggest that individuals of O. alcatraz are part of these parasites’ life-cycle, using them as paratenic or intermediate hosts.